Contribuições dos jogos eletrônicos na construção da linguagem algébrica - Romero, Sandra Aparecida (2007)
Current research investigates whether electronic games improve algebra language learning in 6th grade students of the junior school. Initial hypothesis underpins (1) the existence of electronic games that may be classified as games according to the theoretical referential of conventional games and that (2) the deployment of (educational) electronic games may be a significant asset for learning the language of algebra. The difficulties in the construction of algebra language were initially analyzed and the main characteristics of traditional games were introduced, including such difficulties as defining the term game. The main criteria that the teacher has to keep in mind so that games, in the classroom context, do not lose their playful traits were pinpointed. In other words, the games' principal characteristics, or rather, their intensity and their fascinating power, should be kept. The next section deals with the specific use of games in education and in math teaching, coupled to a brief historical narrative on technological development throughout history. Special emphasis was given to modifications brought about by informatics within the home and to the immersion of the school in cybercultural society which, consequently, may justify the use of electronic games as pedagogical tools. After giving a brief analysis on the importance of electronic games in current society, the "didactic intervention" developed with 6th grade students and their use of electronic games on the Internet at the Freudenthal Institute site (www.fi.uu.nl) were introduced. Selected games, justifications for each selection and the methodology of didactic intervention were discussed. Quantitative and qualitative analyses of results were given according to the theoretical referential employed and remarks on the initial hypothesis and its possibilities were finally debated.